Appendix to Personas in Practice: Adapting Knowledge Worker Actions to Software Engineer - Ford Robinson, Denae; Zimmermann, Tom; Bird, Christian; Nagappan, Nachi (Microsoft, 2016)
This technical report contains supplemental materials to the paper "Personas in Practice: Adapting Knowledge Worker Actions to Software Engineer"